The Labyrinth of Star Formation - Stamatellos, Dimitris (Astrophysics and Space Science Proceedings, 2014)
This volume contains the proceedings from the conference 'The Labyrinth of Star Formation' that was held in Crete, Greece, in June 2012, to honour the contributions to the study of star formation made by Professor Anthony Whitworth of Cardiff University.The book covers many aspects of theoretical and observational star formation: low-mass star formation